Prevalence, Mortality Rate and Risk Factors of Obstetrics-Related Venous Thromboembolism in Africa: A Systematic Review - Nwagha, T U; Ojukwu, C P; Nweke, M; Nwagha, U I (West African journal of medicine, 2025)
Obstetric-related venous thromboembolism (VTE) is common in Africa. However, management has remained suboptimal. Evaluating its epidemiology will aid policy decisions. To evaluate the prevalence, mortality rate and risk factors of obstetrics-related venous thromboembolism in Africa. We searched four databases namely MEDLINE, PubMed, CINAHL, and Academic Search Complete. We undertook independent screening to identify relevant articles. Only peer-reviewed articles written and published in English were included. We fitted a random-effect model to estimate the pooled prevalence and mortality rates, with I2 computed to estimate the degree of heterogeneity. Prevalence of obstetrics-related VTE varied between 2 (per 100,000 deliveries) in 2000 and 248 (per 100,000 births) in 2020. The pooled prevalence was 17 per 100,000 births (95% CI 6-480/100,000 births). Two most important risk factors were immobilization/prolonged travel (OR=2.5 [95% CI 1.4 - 4.5] to 18 (95% CI 2.3-137) and oral contraceptive (OR=15.9, [95% CI 1.9-133.1]). VTE-related maternal mortality ranged from 33 to 286 per 100,000 live births. Moving from 2000 to 2020, there is an increasing trend in the prevalence of obstetrics-related VTE and associated maternal mortality in Africa. The strength of risk factors of obstetrics-related VTE in Africa may not follow a global risk stratification pattern.